THE INCREASE OF RIVER FLUOR CONTENT USING WHITE AND GREEN FLUORIDE STONE - Emilda Sari (Jurnal Riset Kesehatan, 2021)
Fluoride content in water consumed by the people of Mekar Sari Village, Tatah Makmur District, Banjar Regency, South Kalimantan Province is still below the WHO recommendation and the Ministry of Health of Indonesia. This study aims to determine the differences in the ability of fluoride stones from the peat area - Liang Anggang, Banjar Regency and fluoride stones from Tanah Laut area of South Kalimantan in increasing fluoride content in river water. This type of work is analytical research. The experiments were carried out in river water by means of preliminary treatment until the turbidity is less than 5 NTU. Furthermore, the processed water was re-circulated into a “flour increase portable” device to manipulate the processed water with stones containing fluoride. Variations in research include 24 hours, 48 hours and 72 hours recirculation; fluoride stones types were from Liang Anggang area and from Tanah Laut. The results show that green stones from Tanah Laut area can increase fluoride content in processed river water to 0.63 mg / l. This means that the ability of this green stone is lower than that of white stone in increasing fluoride content in processed river water.